Pengaruh Penempatan dan Kompensasi Terhadap Kepuasan Kerja dan Kinerja Karyawan - Kusuma, I Putu Satria Wira; Ardana, Komang (E-Jurnal Manajemen, 2014)
This study aims to determine the direct effect of placement and compensation to job satisfaction , as well as the direct influence of placement , compensation and job satisfaction on employee performance , then to determine the effect of placement and indirect compensation to employee performance through job satisfaction , as well as to know the total effect of placement and compensation on employee performance . The number of respondents who used amounted to 64 people . Collecting data using the method of observation , questionnaires and interviews . The data analysis technique used is the technique of path analysis ( path analysis ) . The results found that , there is a positive and significant influence directly between placement , compensation and job satisfaction directly influence the placement , compensation and job satisfaction on kinerjakaryawan . Furthermore, it was found that indirectly influence the placement and compensation to employee performance through job satisfaction , as well as in total there pengarauh between placement and compensation to employee performance through employee satisfaction.
Keywords: Placement, Compensation, Job Satisfaction, Employee Performance